Resistant Hypertension Secondary to Severe Renal Artery Stenosis With Negative Duplex Ultrasound: A Brief Review of Different Diagnostic Modalities - Vipparla, Navya (J Investig Med High Impact Case Rep, 2020)
Renal artery stenosis is a cause of resistant hypertension, which can present with several features such as severe hypertension, deterioration of renal function (with or without associated angiotensin-converting inhibitor or angiotensin receptor blocker therapy), and flash pulmonary edema. When evaluating for the presence of renal artery stenosis, the most widely utilized imaging modalities are duplex ultrasonography and computed tomography angiography. In this article, we discuss the case of a 77-year-old female who presented with shortness of breath and mild pulmonary edema, secondary to hypertensive emergency. Later, she was diagnosed with renal artery stenosis and underwent stent placement in the left renal artery. Our case highlights the different diagnostic modalities and emphasizes that the most commonly used screening, which is duplex ultrasonography, was performed on our patient but gave a false-negative result, despite high-grade stenosis, which was later diagnosed on computed tomography angiography.